More Than Just a Piece of Cloth: The German "Headscarf " Debate - Sinclair, Stefanie (Implicit religion, 2013)
This article highlights the blurred and often confused nature of the distinction between religious, cultural and political issues, within debates around the legal regulation of Muslim women's dress codes. It focuses on party-political debates in Germany about female Muslim state school teachers' right to wear, or duty to remove, a hijab, and highlights implicit assumptions about the role of religion in German culture, politics, legislation, education and notions of citizenship that have informed this debate.